MAKNA TANDA DALAM INTERIOR RUANG TAMU: STUDI SEMIOTIKA SISTEM TERTUTUP PADA INTERIOR RUANG TAMU LIMA STATUS SOSIAL DI YOGYAKARTA - Wishnu Aji, Artbanu (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2008)
Guest roomin Indonesian houses has a unique position compared with any other room The owner of the house usually sets more decoration in the guest roomas a mean to impress the guest This tendency has a root in Indonesian traditional society where the guest has always been honored and treated well This research aims to reveal the meaning of the guest room interior in five different social groups in Yogyakarta Using semiotic analysis with closed system developed by Bonta the five guest rooms are interpreted with local cultural reference that has been the source of the signs created by each social group The result of this study showes that each social group has its own particular signs that can be associated with their social background The study also reveals five binary oppositional meanings which can be attached in each social group in a contrasting way These meanings are simplicity luxary Elite cammon pride humble artistic plain idealistic realistic progressive conservative and private public.Keywords : Social group Meaning Semiotic